Development of Google Sites-Based Parenting Management Model to Improve the Role of Parents in Shaping A Child’s Character and Development - Lamba, Septhy Saputri; Dwikurnaningsih, Yari; Satyawati, Sophia Tri (LPPM Universitas Pendidikan Mandalika, 2024)
This research aims to develop a Google Sites-based parenting management model to support the role of parents in shaping a child's character and development. This method used research and development with the Borg & Gall model, which involved research, planning, initial product development, field testing, and leading product revisions. The study took place at TK Kristen 03 Eben Heazer, Salatiga, involving school principals, teachers, and parents. Data collection techniques included interviews, documentary studies, observations, and questionnaires. Data analysis utilized qualitative and quantitative descriptive methods. The development of the